Abordagem dos cuidados paliativos nos pacientes pediátricos com doenças onco-hematológicas: um estudo retrospectivo no Hospital das Clínicas da Universidade Federal de Minas Gerais (2009-2011) - Maria Thereza Macedo Valadares (2013)
Objective: To evaluate the approach of palliative care in a tertiary hospital.Methods: Cross sectional study, about the main items of palliative care: approach and prevalence of pain, other symptoms prevalence, participation of a multidisciplinary team, communication between staff and family and limitation of invasive therapy. The sample included patients with onco-hematological diseases who died from January 2009 to December 2011, in a pediatric ward. The Spearman correlation coefficient was used to assess the correlation between age at death and number of symptoms presented by the patient. The nonparametric Mann-Whitney test was used to compare age at death among the group of patients with symptoms up to three and that one with four or more symptoms.Results: Twenty-nine patients were included, 62.1% were male, 45% had hematological diseases/malignancies and 55% had solid tumors. Twenty-seven (93.1%) had disease in progression, without response to curative therapeutic. The median age at death was 10 years. Pain was the most prevalent symptom. Every patient with a report of pain used some kind of pain medication and most used weak and/or strong opioids, 55.2 and 65.5%, respectively. There was no record of pain assessment scales and/or use of non-pharmacological interventions for pain relief.Poor correlation between the number of symptoms and the age at death (r = 0.37, p = 0.05) was observed, in other words, as much as higher patient's age more numerous the symptoms found. When we compared the group of patients with symptoms up to three with the group with four or more symptoms, no significant differences were found in age at death between the two groups (p = 0.14).Patients were followed for general pediatric residents and participation of other professionals was also documented: 86.2% of children were accompanied by social services, 69% by psychology, among others. Two patients died with complications secondary to treatment, 27 died due to disease progression. Among these was explicit description in medical records, by medical staff, about limiting invasive therapy in 26 cases (96.3%). All these decisions were shared with families.Conclusions: The findings of this study demonstrate that the institution, in which it was conducted, despite having no team specialized in pediatric palliative care, presents most of the requirements for the development of a specific program. It was evident the importance of pain management and other prevalent symptoms in children with cancer. For this approach to be effective, the participation of a multidisciplinary team, with real integration between them is essential.